Optimal design of organic Rankine cycle recovering LNG cold energy with finite heat exchanger size - Choi, Hong Wone; Na, Sun-Ik; Hong, Sung Bin; Chung, Yoong; Kim, Dong Kyu; Kim, Min Soo (Energy (Oxford), 2021)
An optimization study, under a size constraint, was carried out for an organic Rankine cycle (ORC) combined with an LNG regasification plant for recovering LNG cold energy. Typically, many researchers approached to an optimization problem by assuming pinch point or minimum approach temperature difference. As a different point of view, the size constraint was considered in that resources such as thermal energy and equipment size are limited in a real problem. Given this situation, adequate allocation of finite resources is an important issue for the system to maximize performance. Thus, the aim of this study is to understand how to properly utilize the resources when LNG cold energy and total conductance of heat exchangers are limited. Accordingly, the influences of heat duty allocation, UA allocation, and superheating a turbine’s intake on net power were mainly taken into account. Results indicate that, when total conductance for system design increases, the ORC should take more heat duty and total conductance should be weighted to an evaporator. In most cases, the size of heat exchangers should be weighted in the order of evaporator, condenser, and trim heater, provided that total conductance for system design is sufficiently available. •The ORC combined with LNG regasification plant was optimized under size constraint.•We examined trade-off among performance related to heat duty and UA allocations.•A trend of optimal allocations was observed subject to a change of size constraint.•Seven types of refrigerants were taken into account under size constraint.